Education, relationships, and place: life choices in the narratives of university master students - Mikhaylova, Oxana; Bochaver, Alexandra; Yerofeyeva, Victoria (Frontiers in Psychology, 2024)
Choice is one of the most roughly defined concepts in contemporary social sciences. Previous studies have elucidated the factors that influence young people's choices in different life situations. However, it is still unclear how young people evaluate these choices and how they integrate them into their biographies. In this study, we examine the narratives of 30 first-year master's students at HSE University with regard to two categories of life choices: those that they perceive as fortunate and those that they perceive as unfortunate. Using a written online survey, the data was collected in the spring of 2022. To categorize the different decision kinds, thematic analysis was applied. Overall, we discovered that narratives about the life choices made by master students concentrated on education, relationships and place.